Analysis of the structure and function of the tomato Solanum lycopersicum L. MADS-box gene SlMADS5 - A. V. Nezhdanova; M. A. Slugina; E. A. Dyachenko; A. M. Kamionskaya; E. Z. Kochieva; A. V. Shchennikova (Вавиловский журнал генетики и селекции)
At all stages of flowering, a decisive role is played by the family of MADS-domain transcription factors, the combinatorial action of which is described by the ABCDE-model of flower development. The current volume of data suggests a high conservatism of ABCDE genes in angiosperms. The E-proteins SEPALLATA are the central hub of the MADS-complexes, which determine the identity of the floral organs. The only representative of the SEPALLATA3 clade in tomato Solanum lycopersicum L., SlMADS5, is involved in determining the identity of petals, stamens, and carpels; however, data on the functions of the gene are limited. The study was focused on the SlMADS5 functional characterization. Structural and phylogenetic analyses of SlMADS5 confirmed its belonging to the SEP3 clade. An in silico expression analysis revealed the absence of gene transcripts in roots, leaves, and shoot apical meristem, and their presence in flowers, fruits, and seeds at different stages of development. Two-hybrid analysis showed the ability of SlMADS5 to activate transcription of the target gene and interact with TAGL1. Transgenic plants Nicotiana tabacum L. with constitutive overexpression of SlMADS5 cDNA flowered 2.2 times later than the control; plants formed thickened leaves, 2.5–3.0 times thicker stems, 1.5–2.7 times shortened internodes, and 1.9 times fewer flowers and capsules than non-transgenic plants. The flower structure did not differ from the control; however, the corolla petals changed color from light pink to magenta. Analysis of the expression of SlMADS5 and the tobacco genes NtLFY, NtAP1, NtWUS, NtAG, NtPLE, NtSEP1, NtSEP2, and NtSEP3 in leaves and apexes of transgenic and control plants showed that SlMADS5 mRNA is present only in tissues of transgenic lines. The other genes analyzed were highly expressed in the reproductive meristem of control plants. Gene transcripts were absent or were imperceptibly present in the leaves and vegetative apex of the control, as well as in the leaves and apexes of transgenic lines. The results obtained indicate the possible involvement of SlMADS5 in the regulation of flower meristem development and the pathway of anthocyanin biosynthesis in petals.